Medya Okuryazarlığı: BBC Panorama Krizi Bağlamında Reddit Kullanıcı Söylemlerinin Analizi. - Aydoğan, Bahar Balcı (Journal of Türkiye Media Academy / Türkiye Medya Akademisi Dergisi)
This study aims to examine Reddit users' comments from a media literacy perspective on the process that escalated into a public crisis in November 2025 following the edited broadcast of Donald Trump's January 6, 2021 speech on the BBC's Panorama program on October 28, 2024. The research seeks to reveal how discourses produced in the digital public sphere are shaped in relation to media credibility, editorial ethics, political polarization, and cognitive biases. Both qualitative and quantitative research methods were employed. A total of 304 Reddit comments that directly referenced the BBC's edited broadcasting practice were selected through purposive sampling and included in the analysis. User discourses were coded through qualitative content analysis, resulting in thematic categories such as media credibility and ethics, political polarization, legal responsibility, and socio-cultural reactions. Within the quantitative phase, frequency distributions, sentiment analysis, types of cognitive bias, and levels of media literacy were calculated and visualized using the Python programming language. The findings indicate that user discourses are largely shaped by negative emotions, confirmation bias, and ideological positioning. Users with lower levels of media literacy tend to produce generalized, decontextualized, and emotionally charged comments, whereas a small number of users with higher media literacy competence are able to evaluate editorial interventions within the framework of ethical principles and institutional responsibility. Moreover, a strong inverse relationship was identified between media literacy and political polarization. Overall, the study demonstrates that media literacy is not merely an individual skill but a structural and transformative civic competence that determines the quality of digital debate during periods of crisis.